Advising Growers in Selection of Heterodera glycines-Resistant Soybean Cultivars - Young, L D (Journal of nematology, 1996)
Female indices were measured on six soybean cultivars with resistance to Heterodera glycines derived from PI 88788. Cultivars were inoculated with four isolates of race 6, 3 of race 9, 2 of race 4, and one of race 14. Changes in female index from slightly < or > 10% of the test cultivars compared to 'Lee' resulted in a change of most of the race designations after at least three generations on 'Essex.' Variation due to race was the greatest source of variation in the analysis of the data and was three to nine times the second largest source of variation. In most cases, female indices for the cultivars within a race were not different (P = 0.05). This study suggests that one cultivar can serve as a type cultivar for a common source ofH. glycines resistance. Value of race designations was demonstrated